Formal procedures in rural development planning: a comparison of selected methods - Kiryluk-Dryjska, Ewa (Zastosowanie formalnych procedur w planowaniu rozwoju obszarów wiejskich: porównanie wybranych metod, 2020)
The objective of this paper is to compare and discuss the results of the multi-objective linear programming and bankruptcy rules applied to a practical structural policy budget allocation problem using the example of the Polish Rural Development Program 2007-2013. The spread, the Gini indexes and the Lorentz curves were used to compare the funds’ dispersion. The results show some similarities between the allocation performed by the linear programming model and the CEL method. Both of the procedures resulted in the allocation concentrated on a limited number of measures, assuring their high financing. Conversely, CEA allocation is the most similar to the actual allocation of the MARD. In both cases the financing is spread among all programs, with a special emphasis on satisfying programs with lower claims. The results demonstrate that, with the use of formal methods, decision-makers can choose if they are willing to set more dispersed or more concentrated budgets
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 64-74
Keywords: fair division; EU funds; rural development; allocation; sprawiedliwy podział; fundusze Unii Europejskiej; rozwój obszarów wiejskich; alokacja